Distance Announcement Using Android Smart Phone and Ultrasonic Distance Sensor - HO CHEN XI, - (Universiti Malaysia Sarawak, 2022)
This project describes the Distance Announcement using an Android Smart Phone and Ultrasonic Distance Sensor. A distance measuring instrument is a device that measure the distance between two or more objects. Distance measurement is necessitating in most of the profession. The major objective of this project is to design a low costs Distance Announcement using an Android Smart Phone and Ultrasonic Distance Sensor. This projects only spends around RM60 to create the device and it is multipurpose. The second objective is to notify the user about the distance measurement by showing on the smart phone. Another objective of this project is to get an accurate measurement so that can be apply in construction field for precise and small measurements. The device has great accuracy and precision. This project shows that the system could measure the distance accurately and display it on the Android Smart Phone.